Electro-Acupuncture Attenuates Chronic Stress Responses via Up-Regulated Central NPY and GABAA Receptors in Rats - Yang, Yu; Yu, Haijie; Babygirija, Reji; Shi, Bei; Sun, Weinan; Zheng, Xiaojiao; Zheng, Jun (Frontiers in Neuroscience, 2021)
Stress can increase the release of corticotropin-releasing factor (CRF) in hypothalamus, resulting in attenuation of gastric motor functions. In contrast, central neuropeptide Y (NPY) can reduce the biological actions of CRF, and in turn weakens stress responses. Although electroacupuncture (EA) at stomach 36 (ST-36) has been shown to have anti-stress effects, the mechanism remains to be investigated. The effect of EA at ST-36 on hypothalamus-pituitary-adrenal (HPA) axis and GI motility in chronic complicated stress (CCS) conditions have not been studied and the inhibitory mechanism of NPY on CRF through gamma-aminobutyric acid (GABA)A receptor need further be investigated. A CCS rat model was set up, EA at ST-36 was applied to the bilateral hind limbs every day prior to the stress loading. Further, an GABAA receptor antagonist was ICV (intracerebroventricular) injected daily. Central CRF and NPY expression levels were studied, serum corticosterone and NPY concentrations were analyzed, and gastric motor functions were assessed. CCS rats showed significantly elevated CRF expression and corticosterone level, which resulted in inhibited gastric motor functions. EA at ST-36 significantly increased central NPY mRNA expression and reduced central CRF mRNA expression as well as the plasma corticosterone level, helped to restore gastric motor function. However, ICV administered of GABAA receptor antagonist significantly abolished these effects. EA at ST-36 upregulates hypothalamic NPY system, NPY may through GABAA receptor, significantly antagonized the overexpressed central CRF and attenuates the HPA axis activities in CCS conditions, and exerted influences on helped to bring back gastric motor function.